MOF-Based Solid-State Batteries: An Ideal Choice for High Safety and Environmental Protection - Chen, Yupu (Scientific Journal of Technology, 2025)
With the widespread application of lithium-ion batteries in fields such as power, energy storage, and consumer electronics, the environmental pollution and resource waste issues caused during their manufacturing and recycling processes have increasingly drawn the attention of all sectors of society. To address the above problems, the research on environmentally friendly battery systems has been put on the agenda. Among them, solid- state batteries have received significant attention from both the academic and industrial communities due to their characteristics of having no organic electrolyte, high safety, and high energy density. In this study, a ZIF-8-PVDF- HFP-IL composite solid electrolyte was prepared by compounding a metal- organic framework (MOF) ZIF-8, a polymer matrix PVDF-HFP, and an ionic liquid (IL). Through various performance tests, it was demonstrated that the ZIF-8-PVDF-HFP-IL composite solid electrolyte exhibits good mechanical strength and thermal stability, and can maintain its shape even at high temperatures (300 °C). Moreover, it self-extinguishes within 1.5 s after combustion, indicating excellent flame retardancy. In addition, the room- temperature ionic conductivity of the ZIF-8-PVDF-HFP-IL composite solid electrolyte reaches 0.36 mS cm⁻¹ , which is 2 - 3 orders of magnitude higher than that of conventional polymer solid electrolytes. Finally, when the ZIF-8- PVDF-HFP-IL composite solid electrolyte was assembled into a pouch battery, the battery could still operate normally after being physically damaged, demonstrating extremely high safety performance. This research verifies the feasibility of the proposed solid electrolyte preparation strategy, has the potential to replace existing liquid lithium-ion batteries, and thus provides a new technical solution to address the environmental pollution and resource waste issues caused by the preparation and recycling of liquid lithium-ion batteries.